Frequency Of Spinal Defects in Fetuses with Ventriculomegaly: Frequency of Spinal Defects in Fetuses with Ventriculomegaly - Hamza Khan, Ameer; Ali, Noraiz; Ul-Hasan , Zain; Yousaf Farooq , Syed Muhammad; Akhtar, Amna; Zawar Zain, Saqib; Ahsan Javed , Ali; Yasir , Adeel; Hashim , Muhammad; Khatera, Bibi; Fatima, Arooba; Iram, Nozaina (Pakistan Journal of Health Sciences, 2022)
Fetal ventriculomegaly (VM) is a dilation of the lateral ventricle. Different patients have different etiologies for fetal ventriculomegaly, which can be idiopathic, structural, or chromosomal. A measurement of 10–15 mm is commonly referred to as mild ventriculomegaly, while measurements of 15–20 and >20 mm and above are defined as moderate and severe ventriculomegaly. Objective: To find the frequency of spinal defects (SD) in fetuses with ventriculomegaly (VM). Methods: It was a cross-sectional analytical study which included 103 pregnant ladies who had evidence of ventriculomegaly visited multiple centers during research period. Convenient sampling method was used. The presence of ventriculomegaly was confirmed using transabdominal probe with frequency 3-5 MHz. Frequency was calculated and crosstabs were made using SPSS version 21.0. Results: Among 103 pregnant patients, frequency of fetal spinal defects was 25.2%. Frequency of ventriculomegaly was as follow: mild ventriculomegaly 43.7%, moderate ventriculomegaly 31.2%, and severe ventriculomegaly 25.2%. Among 103 patients, 25.2% patients had AFI greater than 21. Frequency of mother's H/O any fetal spinal defects in their previous pregnancies was 15.5%. Conclusions: The study concluded that frequency of spinal defects in fetuses with ventriculomegaly was 25.2% and spinal defects occur in those patients who had severe ventriculomegaly (>20mm) and had AFI greater than 25